Curriculum and "New Technologies" in times of globalization - Fernando Cesar Sossai; Geovana Mendonça Lunardi Mendes; José Augusto Pacheco (Universidade Federal de Santa Catarina, 2010)
This essay discusses epistemological arrangements that supposedly inscribe the field of curricular studies in a cosmopolitan agenda of reflection. In addition, we analyze how curricular studies, from the premise of dialog with the phenomenon of globalization, produce increasingly allegorical curricular metaphors, epithets and jargon. In this sense, we also reflect on the reframing of curricula studies as a place of practices of signification, as well as on the ambivalent character that the process of digression about globalization allows in the field itself. In examining these directions, we adopt as a locus of reflection the hybrid curricular contexts of Brazil and Portugal to analyze a basic issue: the semantic equivalence of the much discussed "new educational technologies" as the vehicles of globalization imaginarily prepared to make the school curriculum "current." In this process, we adopt as a reference question the relationship between curriculum and globalization in order to reflect on some of the arguments that have been used to interrogate the field of curricular studies in relation to the opportunities created by the highly promoted technologies capable of allowing transit between the local and the global.